Jigsaw Cooperative Learning and Critical Thinking Performance in Pre-Service Teacher Trainees at ESEF Kenitra, Morocco - Ayoub El Baioui; Latifa Hafdi Idrissi (Journal of English Language Teaching and Linguistics, 2026)
This study examined whether the jigsaw cooperative learning technique improves critical-thinking performance among pre-service teacher trainees at the École Supérieure de l’Éducation et de la Formation (ESEF) in Kenitra. Using a posttest-only randomized control-group design, 120 trainees were initially assigned to either a jigsaw-based instructional condition or a lecture–discussion condition; 113 participants completed the study (60 experimental; 53 control). Critical thinking was measured immediately after an 11-week instructional period using a researcher-developed 34-item, scenario-based multiple-choice post-test (score range: 0–34) administered via Google Forms. The instrument demonstrated satisfactory internal consistency (Cronbach’s α = .877). As score distributions deviated from normality, between-group differences were examined using a Mann–Whitney U test. Findings indicated that trainees in the jigsaw condition achieved higher post-test performance than those in the lecture–discussion condition, suggesting that structured peer interdependence and peer teaching can support stronger critical-thinking performance in pre-service teacher education. These findings imply that teacher-education curricula should move beyond transmission-oriented instruction by embedding structured collaborative routines that make reasoning visible and accountable. It is recommended that teacher-education programs incorporate jigsaw-based activities more systematically in methodology courses and micro-teaching sessions to foster critical thinking in context.